Analisis Sentimen Cyberbullying Pada Media Sosial X Menggunakan Metode Support Vector Machine - Syahira, Melani Alka; Kurniawan, Rakhmat (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
Twitter or the platform now known as social media X is now one of the social networks most popular. Its popularity not only does it have a positive impact but it also has a negative impact on both users and non-users of the X platform. The negative impact is a lot many social media users use it to insult or defame, known as Cyberbullying. Cyberbullying is a deliberate act and occurs virtually through verbal intimidation or ongoing harassment on the internet or social media. Cyberbullying can cause serious emotional impacts for the victim, such as depression, behavior changes, mood swings, and sleep and appetite disorders. To overcome this problem, sentiment analysis using data from X to determine the level of accuracy with the Support Vector Machine algorithm. Data was collected through Crawling as many as 1000 data, then Preprocessing was carried out. After preprocessing, data labeling was carried out manually, there were 157 positive data and 843 negative data. Then, the data was separated into two parts, namely 80% training data and 20% testing data. The results of data processing showed 87% accuracy, 88% precision, 99% recall, and 93% f1-score.